Highly thermally-stable 4, 4′-bis(4″-triphenylsilylphenyl)-1, 1′- binaphthalene as the ultraviolet amplified spontaneous emitter, efficient host and deep-blue emitting material. (July 2016) - Li, Weiling; Xu, Tao; Chen, Guo; Zhang, Hao; Gao, Xicun; Zhou, Xuehua; Huang, Haifang; Fan, Heliang; Cai, Miao; Zhang, Xiaowen; Yang, Lianqiao; Zhu, Wenqing; et al.
Abstract: We report herein the synthesis and characterization of an efficient versatile binaphthyl derivative, 4, 4′-bis(4″-triphenylsilylphenyl)-1, 1′-binaphthalene (SiBN) with a high glass transition temperature of 159.3 °C. Its role as a lasing dye was demonstrated by the amplified spontaneous emission, which exhibited an ultraviolet peak of 397 nm with a low threshold of 20 μJ/pulse. Meanwhile, the lasing film and blue electroluminescent device employing this novel binaphthyl derivative as the host showed superior performances to the reference based on the conventional host 4, 4′-bis(carbazol-9-yl)biphenyl. Finally, extremely stable colour-tunable deep-blue (436 nm/472 nm) organic electroluminescent devices based on SiBN were demonstrated with very high brightness (>7521.2 cd/m 2 ) and high external quantum efficiencies (1.90% for 436 nm and 4.66% for 472 nm emission). The development of such functional versatility materials will be an effective method for reducing the cost of organic photoelectric devices. Graphical abstract: Highlights: A highly thermal stability and functional versatility material was synthesized. An ultraviolet lasing dye with an ASE threshold of 20 μJ/pulse. It is adequate to the role of the host material compared with common host material. Extremely stable colour-tunable blue organic light-emitting devices were obtained.